The Impact of Intellectual Capital and Corporate Governance on Bank Performance in Indonesia (2022–2024) - Muhamad Farhan Azis; Januar Eko Prasetio (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the impact of Intellectual Capital and Corporate Governance on financial performance in banking companies listed on the Indonesia Stock Exchange during the period of 2020–2024. The method used is a quantitative approach to identify the relationship between independent and dependent variables using SPSS for Windows 27. The data used are secondary data in the form of financial reports from banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period of 2020–2024, and the sample was taken using purposive sampling technique. The simultaneous test results show that both Intellectual Capital and Corporate Governance variables, when tested individually, have no significant effect on the financial performance of the companies. However, Intellectual Capital and Corporate Governance, when tested simultaneously, have a significant impact on the companies' financial performance. The study also reveals that the independent variables, namely Intellectual Capital and Corporate Governance, contribute to 34.1% of the variation in the dependent variable, which is the companies' performance. The remaining 65.9% is influenced by other variables outside the regression equation or variables not included in this study model.